Clinically Relevant Drug Interactions with Monoamine Oxidase Inhibitors - Amber N. Edinoff; Connor R. Swinford; Amira S. Odisho; Caroline R. Burroughs; Cain W. Stark; Walid A. Raslan; Elyse M. Cornett; Adam M. Kaye; Alan D. Kaye (Health Psychology Research)
Monoamine oxidase inhibitors (MAOI) are a class of drugs that were originally developed for the treatment of depression but have since been expanded to be used in management of affective and neurological disorders, as well as stroke and aging-related neurocognitive changes. Ranging from irreversible to reversible and selective to non-selective, these drugs target the monoamine oxidase (MAO) enzyme and prevent the oxidative deamination of various monoamines and catecholamines such as serotonin and dopamine, respectively. Tyramine is a potent releaser of norepinephrine (NE) and is found in high concentrations in foods such as aged cheeses and meats. Under normal conditions, NE is unable to accumulate to toxic levels due to the presence of MAO-A, an enzyme that degrades neurotransmitters, including NE. When MAO-A is inhibited, the capacity to handle tyramine intake from the diet is significantly reduced causing the brain to be vulnerable to overstimulation of postsynaptic adrenergic receptors with as little as 8-10 mg of tyramine ingested and can result in life-threatening blood pressure elevations. In addition to adverse reactions with certain foods, both older and newer MAOIs can negatively interact with both sympathomimetic and serotonergic drugs. In general, patients on a MAOI want to avoid two types of medications: those that can elevate blood pressure via sympathomimetic actions (e.g., phenylephrine and oxymetazoline) and those that can increase serotonin levels via 5-HT reuptake inhibition (e.g., dextromethorphan, chlorpheniramine, and brompheniramine). Illicit drugs that stimulate the central nervous system such as ecstasy (MDMA, 3,4-methylenedioxymethamphetamine) act as serotonin releasers. Patient involvement is also crucial to ensure any interaction within the healthcare setting includes making other providers aware of a MAOI prescription as well as avoiding certain OTC medications that can interact adversely with MAOIs.